Comparative Effectiveness of Endovascular Treatment for Acute Ischemic Stroke: A Population‐Based Analysis. Issue 7 (9th April 2020) - Zerna, Charlotte; Rogers, Edwin; Rabi, Doreen M.; Demchuk, Andrew M.; Kamal, Noreen; Mann, Balraj; Jeerakathil, Tom; Buck, Brian; Shuaib, Ashfaq; Rempel, Jeremy; Menon, Bijoy K; Goyal, Mayank; et al.
Abstract : Background: A heterogeneous patient population receives endovascular treatment (EVT) for acute ischemic stroke caused by proximal large‐vessel occlusion every day. We aimed to conduct a population‐based study of EVT in the province of Alberta, Canada, to understand the effectiveness in a complete population and how the magnitude of effect differs from the artificial world of clinical trials. Methods and Results: Within a 3‐year period (April 2015 to March 2018), 576 patients fit the inclusion criteria of our study and constituted the EVT group of our analysis. The medical treatment group of the ESCAPE (Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion With Emphasis on Minimizing CT [Computed Tomography] to Recanalization Times) trial had 150 patients. Thus, our total sample size was 726. We captured outcomes in clinical routine using administrative data and a linked database method. Primary outcome of our study was home‐time. Home‐time refers to the number of days that the patient was back at premorbid living situation without increase in level of care within 90 days of index stroke event. Median age of patients was 70 years (interquartile range, 59–81 years), and 47.8% were women. Median National Institutes of Health Stroke Scale score was 17 (interquartile range, 13–20). EVT was associated with an increased 90‐day home‐time by an average of 8.5 days compared with medical treatment alone using Cragg hurdle regression ( P =0.009). Age and higher National Institutes of Health Stroke Scale score were associated with decreased 90‐day home‐time (both P <0.001). Multivariable logistic regression showed no association between EVT and mortality at 90 days (odds ratio, 0.76; 95% CI, 0.47–1.24). Conclusions: EVT for acute ischemic stroke caused by proximal large‐vessel occlusion was effective in our province‐wide population‐based study and results in an increase of 90‐day home‐time by 8.5 days.